2015
DOI: 10.1093/jpids/piv003
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin-ProducingEscherichia coliin Diarrheal Stool of Swedish Children: Evaluation of Polymerase Chain Reaction Screening and Duration of Shiga Toxin Shedding

Abstract: BackgroundShiga toxin (Stx)-producing Escherichia coli (STECs) are the most common cause of acute renal failure in children. The present study evaluated a 10-year STEC polymerase chain reaction screening regimen in children.MethodsAll routine stool culture specimens from patients below 10 years of age (n = 10 342) from May 2003 through April 2013 in the County of Jönköping, Sweden, were included. Patients were divided in 1 group where analyses of STEC were requested by the clinician (n = 2366) and 1 screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
4
23
0
1
Order By: Relevance
“…This nomenclature reflects both the phylogeny and origin of the toxin as well as its pathogenicity. For example, the presence of Stx2 is strongly associated with hemorrhagic colitis and HUS compared to Stx1 or to the presence of both genes [22,23,62,63]. Within the Stx2 type, Stx2a (formerly named Stx2), Stx2c, and Stx2d activable [64] are associated with a higher risk for human disease [22,65].…”
Section: Shiga Toxins: Structure and Nomenclaturementioning
confidence: 99%
See 3 more Smart Citations
“…This nomenclature reflects both the phylogeny and origin of the toxin as well as its pathogenicity. For example, the presence of Stx2 is strongly associated with hemorrhagic colitis and HUS compared to Stx1 or to the presence of both genes [22,23,62,63]. Within the Stx2 type, Stx2a (formerly named Stx2), Stx2c, and Stx2d activable [64] are associated with a higher risk for human disease [22,65].…”
Section: Shiga Toxins: Structure and Nomenclaturementioning
confidence: 99%
“…The propensity to develop the disease varies according to microbiological and individual characteristics, although the determinants of the disease are not fully elucidated. First, the risk of HUS is greater for O157:H7 E. coli (≈10%) and Stx2v-harboring strains than for non-O157 serotypes and Stx1-harboring strains (≈1%) [22,23,41,43,50,62,63]. Since the first documented outbreaks in the 1980s, the O157:H7 strain has genetically diversified and concurrently acquired enhanced virulence due to bacteriophage-related insertions, deletions, and duplications [106].…”
Section: Propensity To Develop Stec-husmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans can become infected with STEC by ingesting contaminated food or water or by transmission from infected animals or humans [34]. Prevalence of STEC infection in human was 15% by Salmanzadeh-Ahrabi et al, [35], 2.3% by Rajendran et al, [36], 1.7% by van Duynhoven et al, [37], 7% was reported in patients with diarrhoea in Morogoro, Tanzania in 2006 by Raji et al, [38] and 56% by Matussek et al, [39]. The overall prevalence of virulence-associated gene VT1 only, VT2 only, VT1 and VT2 and eaeA were 10.7%, 20.8%, 68.5%, 3.9%, respectively as reported by Wang et al, [31].…”
Section: Discussionmentioning
confidence: 98%